2019
DOI: 10.1503/cjs.009418
|View full text |Cite
|
Sign up to set email alerts
|

The impact of delayed source control and antimicrobial therapy in 196 patients with cholecystitis-associated septic shock: a cohort analysis

Abstract: Background: Cholecystitis-associated septic shock carries a significant mortality. Our aim was to determine whether timing of source control affects survival in cholecystitis patients with septic shock. Methods:We conducted a nested cohort study of all patients with cholecystitisassociated septic shock from an international, multicentre database (1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015). Multivariable logistic regression was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
2
3
0
Order By: Relevance
“…In this study, we found significantly difference in age, APACHE II and SOFA scores, the proportion of cancer and homological cancer between survivors and non-survivors. These results were similar to previous studies [27–29] . In Angus's report, chronic diseases, for instance, the acquired immunodeficiency syndrome, chronic obstructive pulmonary disease and many cancers, are also risk factors for the infections that most commonly precipitate severe sepsis and septic shock [25] .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, we found significantly difference in age, APACHE II and SOFA scores, the proportion of cancer and homological cancer between survivors and non-survivors. These results were similar to previous studies [27–29] . In Angus's report, chronic diseases, for instance, the acquired immunodeficiency syndrome, chronic obstructive pulmonary disease and many cancers, are also risk factors for the infections that most commonly precipitate severe sepsis and septic shock [25] .…”
Section: Discussionsupporting
confidence: 90%
“…These results were similar to previous studies. [27][28][29] In Angus's report, chronic diseases, for instance, the acquired immunodeficiency syndrome, chronic obstructive pulmonary disease and many cancers, are also risk factors for the infections that most commonly precipitate severe sepsis and septic shock. [25] Unfortunately, even if we detect these risk factors of mortality, no management strategies can be changed to improve the outcome in patients with septic shock due to these risk factors can not be treated.…”
Section: Discussionmentioning
confidence: 99%
“…The results of Jackson et al ( 43 ) suggest that septic patients will experience a more substantial mortality benefit when controlled to receive balanced crystalloids in both the emergency department and ICU compared with later when they are admitted to the ICU. This is consistent with other aspects of sepsis care, wherein a faster time to appropriate antibiotic administration and source control are also associated with improved mortality ( 43 , 44 ). A previous analysis showed no correlation between time to completion of a 30 mL/kg IV fluid bolus and mortality, but the type of fluid was not tracked ( 45 ).…”
Section: Discussionsupporting
confidence: 87%
“…However, if left undetected, acute cholecystitis will likely lead to serious complications, including perforation, septic shock, multiorgan failure, and death. 49 When performing POCUS for the evaluation of acute cholecystitis, the presence of gallstones, gallbladder wall thickening, pericholecystic fluid, and sonographic Murphy sign provide diagnostic information. 50 Summers et al 51 reported in a prospective observational study of 164 patients that the test characteristics of POCUS for the detection of acute cholecystitis had a sensitivity of 87% (95% CI, 66-97%) and specificity of 82% (95% CI, 74-88%).…”
Section: Acute Cholecystitismentioning
confidence: 99%
“…Acute cholecystitis is usually diagnosed when the inflammation is localized to the gallbladder. However, if left undetected, acute cholecystitis will likely lead to serious complications, including perforation, septic shock, multiorgan failure, and death . When performing POCUS for the evaluation of acute cholecystitis, the presence of gallstones, gallbladder wall thickening, pericholecystic fluid, and sonographic Murphy sign provide diagnostic information .…”
Section: Circulationmentioning
confidence: 99%